FAKTOR – FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA PERUSAHAAN SEKTOR INDUSTRI DI INDONESIA - Felixianto Rozali; Liana Susanto (Jurnal Paradigma Akuntansi, 2026)
The purpose of this study is to obtain empirical evidence on the impact of profitability, liquidity and firm size on the capital structure of industrial sector firms listed on the Indonesian Stock Exchange for the period 2019-2021. is. The survey sample size was 36 companies from industries selected by a purposive sampling method. Study data were analyzed using multiple linear regression analysis techniques processed with Eviews 9 software. The results of this study show that profitability and firm size do not significantly affect capital structure. Liquidity has a significant negative impact on the capital structure. The implication of this study is that companies can create superior capital structures by paying attention to the components involved to increase investor confidence in their investments.